Facilitating Early-In-Day Discharge for Multiple Sclerosis Patients Treated With Intravenous Methylprednisolone: A Quality Improvement Project. (October 2015) - Probasco, John C.; Hawley, Gina; Burnett, Margie; Gibson, Lorrie; Carter, Kathryn; Harlow, Elizabeth; Russell, Holly; Huffman, Linda; Adams, Jane; Ziegler, Terry; Sporney, Hilary; Levy, Michael; et al.
Background and Purpose: Delays in patient hospital discharge affect care value through costs of prolonged length of stay and barriers to patient flow within the hospital. We sought to facilitate early-in-day discharges (EIDDs) without extending length of stay for inpatients with multiple sclerosis admitted for acute exacerbations and treated with intravenous (IV) methylprednisolone. Methods: We developed a standardized admission order set, a provider checklist, and a patient checklist to better coordinate in-hospital care and discharge planning for patients with multiple sclerosis admitted for IV methylprednisolone treatment. The order set allowed providers to enter an accelerated dosing schedule of methylprednisolone, as appropriate, to ensure administration of the final dose of methylprednisolone in the morning on the anticipated day of discharge. We compared a prospective intervention cohort to a retrospective, preintervention baseline cohort. Results: At baseline (N = 25), 12.0% of patients were EIDD compared to 40.7% of intervention patients (N = 27; P = .03). In all, 85.2% of intervention patients compared to 64.0% of baseline patients were discharged on the same day as last methylprednisolone treatment ( P = .11). No difference was observed in median length of stay and 30-day readmission rate between groups. Conclusions: Use of a standard admission order set as well as provider and patient checklists can facilitate EIDD and hospital bed availability without compromising care quality for a select group of neurology inpatients.